2019
DOI: 10.5713/ajas.17.0753
|View full text |Cite
|
Sign up to set email alerts
|

Partial replacement of soybean meal with different protein sources in piglet feed during the nursery phase

Abstract: ObjectiveEvaluate the partial replacement of soybean meal with different protein sources in piglet feed during the nursery phase in terms of digestibility of feed, nitrogen balance, growth performance and blood parameters.MethodsExperiment I involved 24 crossbred entire male pigs with an initial body weight (BW) of 18.28±0.7 kg and used a randomized complete block design consisting of 3 treatments (fish meal, FM; soybean protein concentrate, SPC; and soybean meal, SBM) and 8 replicates, with 1 pig per experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…According to Moreira et al (2004), feeding programs focus on increasing the use of amino acids and reducing N excretion. Piglets fed HCP showed higher absorbed N, which may be explained by better usage of protein compounds with reduced urea synthesis (Genova et al, 2019). Even though N retention was not increased in these animals.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…According to Moreira et al (2004), feeding programs focus on increasing the use of amino acids and reducing N excretion. Piglets fed HCP showed higher absorbed N, which may be explained by better usage of protein compounds with reduced urea synthesis (Genova et al, 2019). Even though N retention was not increased in these animals.…”
Section: Resultsmentioning
confidence: 82%
“…The increased activity of urea cycle enzymes is essential to convert ammonia, generated during oxidative deamination of protein metabolites, into urea. Therefore, higher PUC could be a result of increased dietary protein concentration (Genova et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The reference concentrations of urea and glucose established for pigs are 15-45 mg/dL and 60-110 mg/dL, respectively (Genova et al 2019). It can be observed that the urea values are close to the established range, but for the glucose concentration the levels were higher than those in the range, even with diets formulated to meet the animal phase requirements.…”
Section: Growth Performance Plasma Parameters and Diarrhea Incidencementioning
confidence: 78%
“…Model 4 was nearly the equivalent of Model 3 by this criterion for the analysis of gain and was preferred for the analyses of FCR and FBW. Other assessments of growth performance by pigs included covariates in the statistical models that were used to analyse the data (Oliveira et al, 2018;Genova et al, 2019;Oliveira et al, 2019). Additionally, the use covariates in statistical models to control the experimental error could minimize the number of experimental units required for robust experimentation (Jacobs et al, 2013).…”
Section: Resultsmentioning
confidence: 99%